Pengaruh Harga dan Digital Marketing terhadap Kepuasan Konsumen dengan Keputusan Berkunjung sebagai Variabel Intervening pada Puncak Lawang - Adila Rahmatul Khaira; Yulasmi Yulasmi; Febri Aldi (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This research aims to find out how much influence price and digital marketing have on consumer satisfaction with the decision to visit as an intervening variable at Puncak Lawang. The method used was accidental sampling, namely visitors to Puncak Lawang. The research results showed that: there is an influence of price on the decision to visit, digital marketing has a significant positive influence on the decision to visit, price has a positive and insignificant influence on consumer satisfaction, digital marketing has a significant positive influence on consumer satisfaction, the decision to visit has a significant positive influence on customer satisfaction, price has a positive and significant influence on consumer satisfaction through the decision to visit as an intervening variable, digital marketing has a positive and insignificant influence on consumer satisfaction through the decision to visit as an intervening variable at Puncak Lawang.